KEANEKARAGAMAN DAN STRUKTUR KOMUNITAS IKTIOFAUNAPADA EKOSISTEM MANGROVE DI AIR BANGIS,KABUPATEN PASAMAN BARAT - Indra Syamson; Ratih Martia Rahmani; Zalmi Rosano; Mesenu; Harisjon; Siti Aisyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Mangrove ecosystems are important habitats for various fish species in coastal and estuarine areas. This study aims to analyze the diversity and structure of ichthyofauna communities in the mangrove ecosystem in Air Bangis, West Pasaman Regency based on salinity gradients. The study was conducted from January–March 2024 using a quantitative descriptive survey method with a spatial approach at three stations representing different salinity gradients, namely Station 1 (Upstream, 3.2 ppt), Station 2 (Estuary, 14.7 ppt), and Station 3 (Mangrove/Coastal, 27.5 ppt). Fish sampling was carried out using gill nets and cast nets. Data analysis included the Shannon-Wiener diversity index (H’), evenness index (E), and Simpson dominance index (C), as well as ANOVA tests and Tukey HSD follow-up tests. The results showed the discovery of 10 fish species with a total of 234 individuals. The highest H’ value was found at Station 2 (H’ = 2.18; medium category), with the highest uniformity value (E = 0.85) and the lowest dominance (C = 0.19). The ANOVA test showed a significant difference in fish community structure between stations (p < 0.05). Salinity gradient was proven to have a significant effect on fish diversity (r = 0.78; R² = 0.61; p = 0.028). The estuary area has the highest ecological productivity and plays an important role as a transitional habitat for ichthyofauna. Management and conservation of the Air Bangis mangrove ecosystem need to be carried out sustainably to maintain the stability of the fish community and the ecological function of the coastal area